Penerapan Metode Example Non Example (ENE) DalamPembelajaran Biologi Di Kelas Xii SMA 10 Kota Jambi - Rosana Nasution (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract: The average percentage of learning results with a value of ≥ 60 grade XII students MIPA3 and the interest in learning biology in the discussion of the structure and replication of DNA before action is 29.41% and the remaining interest study by 30%. It is far from the expected success indicators which is 70% and interest study at 80%, therefore, it is necessary to take action to improve the outcomes and interest of learning students in grade XII MIPA3. The actions taken on this study used the example non example (EnE) method in the learning activity. The action is carried out in two cycles, wherein at each cycle experienced an increase in the average percentage of learning outcomes with a value of ≥ 60 that is in the first cycle to 52, 94% and in the second cycle reaches 73.53%, as well as students ' learning interest increasedin the first cycle to be 44.12% and the second cycle increases significantly 85.29%.